Utilizing Social Media in Developing Business Strategies in the Digital Era - Belynda Athavia Suryawan (Interkoneksi: Journal of Computer Science and Digital Business, 2025)
This discussion includes influence factors, strategies and the use of social media in developing business strategies in the era of digital transformation. Social media is a digital platform that allows users to create, share and interact with content online. Social media allows two-way communication, where users not only receive information but can also provide responses or interact with existing content. The platform is designed to allow users to create personal profiles, add friends or followers, and share content in real-time. Some examples of popular social media include Facebook, Instagram, Twitter, TikTok, and LinkedIn. Digital transformation is a process that organizations implement to integrate digital technology in all areas of business. This process fundamentally changes the way organizations deliver value to customers. This article explains that the use of social media is important to attract consumers and direct them to communicate electronically and conventionally. Successful use of social media requires a holistic approach, continuous adaptation and rapid response to changes in the digital environment. By designing and executing an effective digital strategy, organizations can improve visibility, customer engagement and overall business results.